Transfer Technology of Laser Engraving Machine for Vocational School in Tegal District - bin abd wahid, Khairul Anuar; Agus Shidiq, Muhammad; Fajar Sidik, Muhamad; Renggani Wilis, Galuh; Santoso, Irfan (Universitas Ahmad Dahlan, 2023)
Background: The problems and challenges that occur in Vocational High Schools (SMK) today are curriculum used is not aligned with the competencies, SMK graduates are not absorbed in the business world and the industrial world, the lack of quality products, competency test facilities, cooperation between companies, government agencies, the business world, and universities. Some of the weaknesses can be overcome through synergy between universities and vocational schools through Community Service activities, one of which is regarding CNC-based machines. Contribution: The contributionof this program is that the Pancasakti University of Tegal, especially the Faculty of Computer Science Engineering in collaboration with SMK Negeri 1 Bumijawa, will carry out learning activities for laser engraving machine training to enhance students' knowledge and experience. Method: The learning model used is theory and practice. The theory is given before practical learning or integrated during practice and at the last meeting an evaluation is held. Results: Training activities through this community service program are divided into several activities, including socialization of the laser engraving training program, Implementation of Theory and practice regarding Laser Engraving Technology, Post-Training Evaluation. Conclusion: The conclusion of this program states that the participants can increase their knowledge and understanding of laser engraving machine technology